Simulasi Computational Fluid Dynamics (CFD) untuk Optimalisasi Proses Perekatan pada Oven Bambu Laminasi - Bahari, Galuh; Septhia Irawati, Inggar; Aris Hendaryanto, Ignatius; Ayu Putri Pratiwi, Ilham; Krisnaputra, Radhian; Sugiyanto; Wijoyo, Joannes Bimo (Infotekmesin, 2025)
The utilization of bamboo in architecture and construction as an eco-friendly alternative to wood is steadily increasing. While ovens are crucial tools in the production of laminated bamboo, particularly for heating during the bonding process, research on ovens specifically designed for bamboo lamination remains scarce. This study aims to optimize the design of laminated bamboo ovens using Computational Fluid Dynamics (CFD) simulations to achieve uniform heat distribution and maximize thermal efficiency. Three design iterations were tested: Iteration 1 with an air velocity of 4 m/s, Iteration 2 with 1.5 m/s, and Iteration 3 with 3 m/s. The results revealed that Iteration 1 exhibited uneven heat distribution, with initial temperatures reaching 1175 K before dropping sharply to 800 K. Iteration 2 showed slower initial heating, achieving a final temperature of 360 K, but heat distribution remained suboptimal. Iteration 3 delivered the best performance, achieving uniform and stable heat distribution near the target temperature of 473 K (200 Â°C). Overall, Iteration 3 demonstrated the most efficient thermal performance, not only meeting the target temperature with consistent heat distribution but also enhancing the overall heating efficiency of the oven.